2003
DOI: 10.1080/00480169.2003.36370
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different combinations of lignocaine, ketoprofen, xylazine and tolazoline on the acute cortisol response to dehorning in calves

Abstract: Combining ketoprofen and local anaesthesia minimised the cortisol response, and by inference the pain-induced distress, following amputation dehorning in calves. Xylazine reduced the initial cortisol response to dehorning but not as much as when local anaesthesia was also given. The increase in cortisol concentration from 3-8 h after dehorning in calves given xylazine alone or in combination with local anaesthesia suggests that calves experienced pain-induced distress during this time and that xylazine had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 30 publications
5
32
2
Order By: Relevance
“…A combination of ketoprofen and lidocaine (Stafford et al, 2003;McMeekan et al, 1998), phenylbuthazone plus lidocaine (Sutherland et al, 2002) and flunixinmeglumine plus lidocaine , have been shown to control pain after scoop dehorning. Similar results were obtained in hot-iron dehorned animals treated with ketoprofen associated with lidocaine (Faulkner and Weary, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A combination of ketoprofen and lidocaine (Stafford et al, 2003;McMeekan et al, 1998), phenylbuthazone plus lidocaine (Sutherland et al, 2002) and flunixinmeglumine plus lidocaine , have been shown to control pain after scoop dehorning. Similar results were obtained in hot-iron dehorned animals treated with ketoprofen associated with lidocaine (Faulkner and Weary, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It caused a significant but short-lived rise in cortisol that was largely back to baseline levels 2-3 hours after surgery. Local anaesthesia reduced struggling during the procedure and pain-related behaviours and plasma cortisol rose for a few hours afterwards, but only the combination of local anaesthesia and a NSAID (ketoprofen, meloxicam or carprofen) effectively controlled pain (Stafford et al, 2003;Stilwell et al, 2007Stilwell et al, , 2012Heinrich et al, 2010).…”
Section: Castrationmentioning
confidence: 99%
“…In piglets, several techniques for the use of local anaesthetics were described to provide shortterm analgesia (White et al, 1995;Haga and Ranheim, 2005;Ranheim et al, 2005;Haga et al, 2006;von Borell et al, 2009). Before disbudding calves and dehorning in cattle and goats, it is recommended to sedate the animal (McMeekan et al, 1999;Stafford et al, 2003;Stewart et al, 2009) and to administer a local anaesthetic (Lepkova et al, 2007). Nevertheless, sedated calves could be unable to react to pain due to strong muscular relaxant effect of xylazine (Stilwell et al, 2010).…”
Section: Soothe Pain Caused By Procedures Considered Unavoidablementioning
confidence: 99%